2015
DOI: 10.15288/jsad.2015.76.307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mother–Daughter Attachment on Substance Use: A Longitudinal Study of a Latina Community-Based Sample

Abstract: ABSTRACT. Objective: Advancing our initial, cross-sectional study, which showed that adult Latinas' mother-daughter attachment relates to their substance use, the current, longitudinal study tests whether mother and daughter attachment scores at baseline predict their substance use over time. Method: We analyzed data from a convenience sample of 133 Latina adult mothers (mean age = 52 years, SD = 10) and 133 Latina adult daughters (mean age = 27, SD = 9) at baseline and at 5-year and 6-year follow-ups after ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…In other words, women who were able to maintain social affiliations with others while adhering to the belief that Latina women should be subordinate and self-silence to maintain harmony may have not experienced the distress felt by their peers who also strongly endorsed the subordinate/self-silencing construct but have less attachment to social network. Overall, the present study’s findings extend findings from past studies that found a positive link between attachment to family and increased psychological well-being among Latina/o immigrants (e.g., De La Rosa et al, 2015; Parsai et al, 2009) to young women who recently immigrated.…”
Section: Discussionsupporting
confidence: 88%
“…In other words, women who were able to maintain social affiliations with others while adhering to the belief that Latina women should be subordinate and self-silence to maintain harmony may have not experienced the distress felt by their peers who also strongly endorsed the subordinate/self-silencing construct but have less attachment to social network. Overall, the present study’s findings extend findings from past studies that found a positive link between attachment to family and increased psychological well-being among Latina/o immigrants (e.g., De La Rosa et al, 2015; Parsai et al, 2009) to young women who recently immigrated.…”
Section: Discussionsupporting
confidence: 88%
“…The intervention targeted communication competencies such as disclosure, empathy, and support as they were previously linked to emotional closeness in Mexican American mothers and daughters with obesity 30. Although research on the role of relational functioning in weight-related behaviors among Mexican American mothers and daughters in adulthood is scarce, studies have shown that adult attachment (ie, high in communication quality and feelings of trust and low in degree of alienation) between Latinx mothers and daughters serves to mutually protect against other unhealthful behaviors 44–46. These findings further support the value of strengthening relational functioning when promoting health behaviors to intergenerational Latinx families.…”
Section: Discussionmentioning
confidence: 67%
“…Yet, empirically based studies of social support among Latina adults are scarce (Cruza-Guet, Spokane, Caskie, Brown, & Szapocznik, 2008). The few existing studies report that Latinas who receive tangible and emotional support and have strong attachments to their families cope better with stress and report less alcohol and illicit drug use compared to Latinas with no support (Barrera, Biglan, Ary, & Li, 2001; Canino et al, 2008; De La Rosa et al, 2015; Lopez et al, 2008; Schwartz et al, 2008; Vega & Sribney, 2003). …”
Section: Interpersonal Determinantsmentioning
confidence: 99%